Antimicrobial activity of Origanum vulgare L. essential oil and its effects on fungal gene expression - Yan Li; Lu He; Zhiwei Xue; Yu Liang; Jiaying Jiang; Yiyan Wei; Huisi Li; Huimin He; Rongjun Li (PLoS ONE, 2025)
Origanum vulgare L. (oregano) essential oil showed strong antimicrobial potential, effectively inhibiting the growth of various microorganisms. In our study, oregano essential oil inhibited the growth of Staphylococcus aureus with a minimum inhibitory concentration (MIC) of 3.13 µL/mL and Bacillus cereus at 6.25 µL/mL. Peronophythora litchii growth was completely suppressed by oregano essential oil at a concentration of 12.5 µL/mL over a period of 7 days. GC-MS analysis identified carvacrol as the dominant component of the oregano essential oil. Transcriptomic analysis revealed that treatment of P. litchii with oregano essential oil resulted in 9,710 differentially expressed genes (DEGs) compared to the control. GO analysis indicated that these DEGs were primarily associated with glutathione metabolic processes, cytosolic ribosome function, and ubiquitin-like protein peptidase activity. Additionally, KEGG pathway analysis showed significant enrichment in proteasome, ribosome, and oxidative phosphorylation pathways. These findings demonstrate the potent antimicrobial efficacy of oregano essential oil against both bacterial pathogens and P. litchii, highlighting its promise as a natural antimicrobial agent.